Recreational fishing as a source for the monitoring of a critically endangered shark in southern Brazil - Santos, Paulo Roberto Santos dos [UNESP] (Elsevier, 2021)
This study tested the use of information collected by anglers for the fisheries monitoring of a Critically Endangered shark in southern Brazil. Catch records of Mustelus fasciatus, Critically Endangered at national and global levels, were obtained from local anglers and tourists in five cities in the main area of occurrence of the species in Brazil. Although they were not comparable due to differences in effort, area and fishing gear, results showed an increase in the number of capture records in relation to the data available in the last two decades (from 4 to 32). Adult females and neonates were highest in catches during spring and summer. There was a high percentage of data recovery (total length, total weight, sex and stage of development) and release rate, which indicates that recreational fishing is an important generator of information for this endangered species. Strategies for applying monitoring in the area are discussed.
Keywords: Conservation; Endemic species; Striped smooth-hound; Unreported catches